Theoretical study of the decomposition pathways and products of C5- perfluorinated ketone (C5 PFK) - Yuwei Fu; Xiaohua Wang; Xi Li; Aijun Yang; Guohui Han; Yanhui Lu; Yi Wu; Mingzhe Rong (AIP Advances, 2016)
Due to the high global warming potential (GWP) and increasing environmental concerns, efforts on searching the alternative gases to SF6, which is predominantly used as insulating and interrupting medium in high-voltage equipment, have become a hot topic in recent decades. Overcoming the drawbacks of the existing candidate gases, C5- perfluorinated ketone (C5 PFK) was reported as a promising gas with remarkable insulation capacity and the low GWP of approximately 1. Experimental measurements of the dielectric strength of this novel gas and its mixtures have been carried out, but the chemical decomposition pathways and products of C5 PFK during breakdown are still unknown, which are the essential factors in evaluating the electric strength of this gas in high-voltage equipment. Therefore, this paper is devoted to exploring all the possible decomposition pathways and species of C5 PFK by density functional theory (DFT). The structural optimizations, vibrational frequency calculations and energy calculations of the species involved in a considered pathway were carried out with DFT-(U)B3LYP/6-311G(d,p) method. Detailed potential energy surface was then investigated thoroughly by the same method. Lastly, six decomposition pathways of C5 PFK decomposition involving fission reactions and the reactions with a transition states were obtained. Important intermediate products were also determined. Among all the pathways studied, the favorable decomposition reactions of C5 PFK were found, involving C-C bond ruptures producing Ia and Ib in pathway I, followed by subsequent C-C bond ruptures and internal F atom transfers in the decomposition of Ia and Ib presented in pathways II + III and IV + V, respectively. Possible routes were pointed out in pathway III and lead to the decomposition of IIa, which is the main intermediate product found in pathway II of Ia decomposition. We also investigated the decomposition of Ib, which can undergo unimolecular reactions to give the formation of IV a, IV b and products of CF3 + CF-CF3 in pathway IV. Although IV a is dominant to a lesser extent due to its relative high energy barrier, its complicated decomposition pathway V was also studied and CF3, C = CF2 as well as C-CF3 species were found as the ultimate products. To complete the decomposition of C5 PFK, pathway V I of Ic decomposition was fully explored and the final products were obtained. Therefore, the integrate decomposition scheme of C5 PFK was proposed, which contains six pathways and forty-eight species (including all the reactants, products and transition states). This work is hopeful to lay a theoretical basis for the insulating properties of C5 PFK.